2017
DOI: 10.1080/09286586.2017.1418386
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey of visual impairment and its correlates in Mahabubnagar district, Telangana State, India

Abstract: Visual impairment was common in Mahabubnagar district, was mostly avoidable, and was correlated with poverty markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…Considering results from population-based studies, this does not seem to be high. For example, data from India using the WG questions in a cross-sectional study suggested that 25% of those people with visual impairment also had moderate or severe hearing difficulties [11]. Also, a survey amongst adults registered with visual impairment in the UK suggested that “43% reported having hearing difficulties” [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering results from population-based studies, this does not seem to be high. For example, data from India using the WG questions in a cross-sectional study suggested that 25% of those people with visual impairment also had moderate or severe hearing difficulties [11]. Also, a survey amongst adults registered with visual impairment in the UK suggested that “43% reported having hearing difficulties” [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, people with other disabling conditions are often more affected by visual problems because of the association of visual impairment and co-morbidities or intersecting disabilities, such as those caused by hearing difficulties, mental illness, etc. [11,12,13]. For example, people with Down syndrome have higher risks of developing co-morbid conditions such as refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of visual impairment among adults aged ≥ 18 years in this study was 16.8% (95% CI: 13.5, 20.2%) which is higher than other studies done in South Sudan (11.8%) [10], Cape Town South Africa (7.2%) [16], Sokoto state of Nigeria (11%) [17], Atakunmosa, South Western Nigeria (7.4%) [18], Bangladesh (9.3%) [19], Malaysia (9.2%) [20], South Korea (4.3%) [21], East Delhi district of India (11.4%) [6], Mahabubanagar district of India (8.4%) [22], Iran (1.39%) [23] and Botucato, Brazil (7.4%) [24].…”
Section: Discusionmentioning
confidence: 99%
“…Prevalence of visual impairment among adults aged 18 years in this study was 16.8% (95% CI: 13.5%, 20.2%) which is higher than other studies done in South Sudan (11.8%) [9], Cape Town South Africa (7.2%) [15], Sokoto state of Nigeria (11%) [16], Atakunmosa, South Western Nigeria (7.4%) [17], Bangladesh (9.3%) [18], Malaysia (9.2%) [19], South Korea (4.3%) [20], East Delhi district of India (11.4%) [5], Mahabubanagar district of India (8.4%) [21], Iran (1.39%) [22] and Botucato, Brazil The prevalence of visual impairment in this study is lower than the studies reported by Upper Egypt (38.8%) [8], Cocoa farmers of Ghana (22.7%) [7], Saudi (23.5%) [24] and rural areas of Coastal Karantaka, India (25.7%) [6].…”
Section: Discussionmentioning
confidence: 99%